Experimental lab propose of different data acquisition techniques of time measurement in physics teaching - Freitas-Lemes, P.; Vilela, D.; Monteiro, M. A.A. [UNESP]; Germano, J. S.E. (My University, 2018)
It promotes an increase in the students' motivation when facing this new teaching-learning technique. In this paper, the active methodology has been applied to an experiment related to time measurement processes. The students are asked to conduct a comparative study using four (4) different techniques of time measurements for a car running down on an inclined surface. The challenge is to identify and justify, from the data obtained, the most efficient technique for the proposed physics experiment.
Proposta de atividade experimental de medida de tempo em laboratório de ensino de física
Keywords: Measures time; Photogate; Stopwatch; Tracker software; Video analysis